Conhecer, vivenciar, desejar: "perejivanie" no ensino em francês - Freire, Gabriela Barbosa Amarante de Mello (2010)
This research is within the realm of Applied Linguistics area and aims to investigate the role of affection in the teaching-learning activity in an International Language. Developed in a Multicultural Education Project (Projeto Educação Multicultural) created by the language research group known as LACE (Linguagem em Atividades no Contexto Escolar Language in Activities in School Contexts), this investigation about the practice of this researcher-teacher seeks to understand critically the role of affective-cognitive aspects in the participation of teenage students in classes taught in French, held at an institute that promotes several educational activities for underprivileged children and youth. To achieve this goal, the main theoretical axis is rooted in the Theory of Socio-Cultural-Historical Activity as postulated by Vygotsky and Leontiev, according to which the human mind is constituted through a social-cultural-historical process. The methodology adopted was the Critical Collaborative Research, for it conceives that transformation only takes place through active joint participation in the negotiation of senses and meanings. Language is seen here through the perspective of dialogic analysis of discourse, based on the concepts of Bakhtin and the Circle, the analysis of discourse according to Bronckart and conversation analysis as proposed by Kerbrat-Orecchioni. The results indicate a major influence of affective issues in the action of the students in the classroom and also indicate that by experiencing emotionally relevant cognitive experiences (perejivanie), the desire to learn through French became latent. This work made it possible to act in the constitution of the subject in two languages towards their cognitive, affective and cultural development expanding their ways to act in the world in which they live in so they could learn, live, and dream with realities perhaps not yet envisioned